SISTEMA DE GESTIÓN DEL CONOCIMIENTO BASADO EN ESTÁNDARES DE ALTA CALIDAD PARA UN PROGRAMA EDUCACIÓN SUPERIOR - Cristian Felipe Castaño Devia; Geraldin Quintero Ruiz; Edgar Duarte Forero (Revista Ingeniería, Matemáticas y Ciencias de la Información)
Knowledge management is a useful tool for the competitiveness of many organizations. The higher education sector isparticularly oriented towards adherence to this type of schemes, since its nature implies constant institutional learningbased not only on its own experience but also on the exchange of knowledge in the academic environment. In Colombia,higher education institutions perceive an opportunity for improvement in the high quality standards of the NationalAccreditation Council, which requires an infrastructure oriented to the strategic knowledge management. This articlepresents the experience of implementing a prototype of a knowledge management system in a higher educationundergraduate program. It describes the phases of the process and its relationship with the technological platform thatsupported the development. The conclusions highlight the advantages of the exercise, emphasizing institutional learning,the importance of the technological platform and, finally, reflections on knowledge management as a fundamental axisof accreditation processes.